Implementation of geographic information system for district and city poverty data distribution using the rational unified process in West Java / Agnia Dwi Khasanah and R.A.E Virgana Targa Sapanji - Dwi Khasanah, Agnia; Targa Sapanji, R.A.E. Virgana (UiTM Cawangan Perlis, 2021)
Poverty is a fundamental problem that several districts and cities have, especially in West Java province. One important aspect to support the Poverty Reduction Strategy is the availability of poverty data that is accurate and on target with good visualization so that it can facilitate the data analysis process. A website-based Geographic Information System is the right solution for mapping the distribution of poverty data. Making this website using software development methods and the Rational Unified Process (RUP) with the Unified Modeling Language (UML) modeling language tool. For the maps, making process using Quantum GIS software and database storage using PostgreSQL. This website is expected to make it easier for the public to find the latest information and analyze poverty data, especially in districts and cities in West Java.